History Education and the Security Community Building in the Western Balkans: A Critical View - Lakić, Nikola (Journal of Regional Security, 2018)
Definitional properties of the security community’s “dependable expectations of peaceful change” exist whenever neither side makes further violence unimaginable. School education in the Western Balkans intensifies the thinking that hostility and conflicts are natural and immutable and makes understanding of war as something inevitable and justified. In this article I draw on Pinar Bilgin’s claim that unfulfilled potential in terms of knowledge and ideas that already exist in the region could help popularize the cause for a security community and facilitate its creation. By adopting immanent critique, a methodological orientation of the Welsh School, in the analysis of the Balkan Conferences (1930–1933) I demonstrate that factual manipulation of history has historically been frequently adopted by Balkan state elites in their permanent desire to build hegemony around ethno-centrism. It was briefly proposed at the Second and Third Conferences that new history textbooks that would overcome ethnocentrism and deepen the trust between the Balkan populations should be introduced in order to achieve rapprochement. In this article I argue that community-minded emancipatory education which adopts multi-perspective methodology and reflective pedagogy harbor crucial potential for further promotion of sustainable peace, facilitating trust in the Western Balkans and inducing the citizens to think of themselves as belonging to a single region.